Controls on coastal flooding in the southern Baltic Sea revealed from the late Holocene sedimentary records - Leszczyńska, Karolina; Stattegger, Karl; Moskalewicz, Damian; Jagodziński, Robert; Kokociński, Mikołaj; Niedzielski, Przemysław; Szczuciński, Witold (My University, 2022)
Climate change and related sea-level rise pose significant threats to lowland coasts. However, the role of key controlling factors responsible for the frequency and landward extent of extreme storm surges is not yet fully understood. Here, we present a high-resolution sedimentary record of extreme storm surge flooding from the non-tidal southern Baltic Sea, spanning two periods: 3.6–2.9 ka BP and 0.7 ka BP until present. Sediments from coastal wetland, including sandy event layers, were analyzed by sedimentological (grain size, loss-on-ignition, micromorphology), geochronological (14C), geochemical (XRF), mineralogical (heavy minerals) and micropaleontological (diatoms) methods. The results show that both periods were characterized by high-frequency of storm surge flooding, in order of 1.3–4.2 events per century. These periods correlate with phases of enhanced storminess in northwest Europe and took place during both rising and fluctuating sea levels. The study shows that the frequency and landward extent of coastal inundation, largely depended on the development of natural barriers (e.g. beach ridges and aeolian foredunes). Thus, in the context of the future coastal storm-surge hazard, the protection of existing coastal barriers and their morphology is essential.
Keywords: coastal zone; storms; Baltic Sea; Puck Bay; Mechelinki; sedimentary record; coastal sediments; wetland; Late Holocene; event deposits; radiocarbon dating; sediment geochemistry; micromorphology; grain size analysis; diatoms; heavy minerals; storm surge; storm climate; coastal protection; sea level change; coastal floods; geohazards; natural hazards; coastal development